The Effect of Curing Mode on the Parameters of Molecular Meshes of Epoxy and Polyester Copolymers - Irina N. Vikhareva (Chemistry Proceedings, 2024)
The establishment of the patterns of formation and structure of mesh polymers, as well as the methods of their controlled synthesis, makes it possible to rationally manage the technological processes of obtaining and processing materials based on them. This paper determines the possibility of directional variation in the parameters of the molecular grid of epoxy and polyester resin copolymers using a polyamide hardener. For this purpose, the influence of temperature regimes on the curing mixing technology of the original components was studied. The values of the Huggins constants were initially calculated. For this purpose, the swelling of copolymers in chloroform, xylene, dimethylformamide and acetone was studied. Taking into account the thermodynamic criteria, based on the results obtained, a solvent was selected that provides optimal swelling conditions for the synthesized copolymer. Experimental data describing the process of collecting copolymer samples were obtained. Using the Florey equation, the parameters of the structural grids of the developed polymer compositions were calculated.